Aplicaciones y limitaciones de la categoría de género - Maier, Elizabeth (Frontera Norte, 2017)
El presente artículo examina los orígenes teóricos de la categoría de género, las particularidades identitarias de las académicas que aportaron a su elaboración, la vinculación de dicha categoría con los movimientos feministas en los países altamente industrializados y, finalmente, sus aplicaciones y limitaciones frente a la problemática de la mayoría de las mujeres en América Latina. La pregunta silenciosa que orienta al ensayo es ¿qué significan los impactos de otras dimensiones identítarias -como clase y etnicidad- sobre la categoría de género como un instrumento autónomo de interpretación social? ABSTRACT This article examines the origins of gender as an analytical category It; focuses on the etnic and class characteristics of the women who contributed to its development as a tool for historical, social, and cultural! understanding. It also emphasizes the links between the development of gender as a social category and the evolution of feminist movements in the more industrialized countries. Finally, the text contemplates the applications and limitations of gender as an interpretative category for the situation and condition of the majority of Latin American;women. The question that underlies this essay is the following. What are the implications of other identity axis, such as class or ethnicity, on gender as an autonomous category for social analysis?